On Neutrosophic Implications - Said Broumi; Florentin Smarandache (Neutrosophic Sets and Systems, 2014)
In this paper, we firstly review the neutrosophic set, and then construct two new concepts called neutrosophic implication of type 1 and of type 2 for neutrosophic sets. Furthermore, some of their basic properties and some results associated with the two neutrosophic implications are proven.